Trust in the central bank and inflation expectation - Dimitris Christelis; Dimitris Georgarakos; Tullio Jappelli; Maarten van Rooij (European Central Bank (ECB), 2020)
Using micro data from the 2015 Dutch CentERpanel, we examine whether trust in the European Central Bank (ECB) influences individuals' expectations and uncertainty about future inflation, and whether it anchors inflation expectations. We find that higher trust in the ECB lowers inflation expectations on average, and significantly reduces uncertainty about future inflation. Moreover, results from quantile regressions suggest that trusting the ECB increases (lowers) inflation expectations when the latter are below (above) the ECB's inflation target. These findings hold after controlling for people's knowledge about the objectives of the ECB.
Keywords: D12; D81; E03; E40; E58; 330; Consumer expectations; inflation uncertainty; anchoring; trust in the ECB